A theoretical and empirical analysis of shopping mall formation in Istanbul, Turkey - Odabaş, Meltem. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2012., 2012)
This study aims to analyze the reasons behind the excessive development of shopping mall in Turkey by focusing on the Istanbul case. In order to clarify the economic reasoning behind the emergence of this new type of retail place in an urban city which is already full of traditional retail places–bazaars, arcades, etc.–, the study proceeds in two main branches: first, in the theoretical part, the economic literature is reviewed in order to demonstrate the distinction between clustering in a shopping mall from other retail places. Next, in the empirical part, the shopping mall development in Istanbul is examined in order to link the theoretical results to what is observed in reality. Supported with focus group studies and in-depth interviews, the general argument is that shopping malls provide firms and consumers with services that are not available in other retail places—an argument leads us to make the claim that malls should be seen as “clubs”. On consumers’ side, they provide parking and security services and extra entertainment activities within a clean and orderly environment in order to attract them. Considering firms, on the other hand, the mall developers help them to overcome some obstacles –such as large-sum financial credit and receiving construction approvals from the urban planning authorities. In that regard, the study argues, entrepreneurs use their advantage on power and network relations, which necessitates their existence as the service facilitator in the mall. This necessity gains further importance in the Istanbul case, due to the lack of commercialized plots in the areas that are close to central business districts.
Keywords: Shopping malls -- Turkey.